Váha parametru TOPSIS techniky a jeho vplyv na hodnotenie obcí v Slovenskej republike - Vavrek, Roman (Univerzita Pardubice, 2017)
Efficient use of funds is the current challenge for operators both private and public sectors. In Slovakia the management of municipalities is governed only by law, that the main and only criterion considers the indebtedness of the village. The goal of the paper is to offer an alternative view of the legal assessment of the economic communities in the form of a comprehensive assessment of management of the municipality. Post characterizes TOPSIS technique as a suitable alternative for a comprehensive assessment of the management of municipalities in 2014, and this technique is applied to a set of villages in the Prešov Region (663) at two levels - at the same and adapted monitored indicators. Within the article the best management of municipalities according to selected criteria is ranked. The results of applications are further statistical examined to identify the impact of the indicators, as well as identification of observed correlation.
Weight of TOPSIS technique parameter and its impact on assessment of municipalities in Slovak Republic
Keywords: local self-government; municipality; Prešov district; TOPSIS technique; multicriterial evaluation; indicators weight; H71; H72; G28; C39; C62